Between the Raj and Raja: Taking Śakuntalā on Tour in Colonial India. Issue 1 (May 2017) - Kulkarni, Kedar A.
This article is about the performative effects of the Abhijñānaśākuntalam, more popularly known as Shakuntala, in western India during the nineteenth century.Noting the play's importance for various oriental discourses and romanticisms across Europe, this article instead charts the play's interpolation of various historical tropes and social issues that become legible through the play's broader theatrical and performative contexts within India. Issues such as a feeling of social fragmentation, the disintegration of Princely (Kingly) power in colonial India, and tense relations between Brahmans and Princes became legible through this play, its performances, and its circulation. Far from the imaginative abstraction that it may have been for its occidental audiences, Shakuntala, in India, easily became resonant with and reproduced various local concerns, making them legible and felt through performance.